P153MicroRNAs involved in cardioprotection by ischemic pre- and postconditioning: ProtectomiRs. (15th July 2014) - Varga, ZV; Zvara, A; Farago, N; Pipicz, M; Gaspar, R; Gorbe, A; Puskas, GL; Csont, T; Thum, T; Ferdinandy, P
Abstract: Purpose: We aimed to characterize early changes in microRNA expression in acute cardioprotection by ischemic pre- and postconditioning in rat hearts. Methods: Hearts isolated from male Wistar rats were subjected to i) time-matched non-ischemic perfusion, ii) ischemia/reperfusion (30 min coronary occlusion and 120 min reperfusion), iii) preconditioning (3x5 min coronary occlusion) followed by ischemia/reperfusion, or iv) ischemia/reperfusion with postconditioning (6x10s global ischemia/reperfusion at the onset of reperfusion, respectively. Infarct size was significantly reduced by both interventions. Results: Out of 350 different microRNAs assessed by microarray analysis, 147-160 showed detectable expression levels. As compared to microRNA alterations induced by ischemia/reperfusion vs. time-matched non-ischemic controls, 5 microRNAs were significantly affected by both pre- and postconditioning (microRNA-125b*, 139-3p, 320, 532-3p, 188), 4 microRNAs by preconditioning (microRNA-487b, 139-5p, 192, 212), and 9 by postconditioning (microRNA-1, let-7i, let-7e, let7b, 181a, 208, 328, 335, 503), respectively. Expression of randomly selected microRNAs was validated by QRT-PCR. By a systematic comparison of the direction of microRNA expression changes in all groups, we identified microRNAs, specific mimics or antagomiRs of which may have pre- and postconditioning-like cardioprotective effect (protectomiRs). Transfection of selected protectomiRs (mimics of microRNA-139-5p, -125b*, and let-7b) into cardiac myocytes subjected to simulated ischemia/reperfusion showed significant cytoprotective effect. Conclusions: This is the first demonstration that ischemia/reperfusion-induced microRNA expression profile is significantly influenced by both pre- and postconditioning, which shows the involvement of microRNAs in cardioprotective signaling. Moreover, by analysis of microRNA expression patterns in cardioprotection by pre- and postconditioning, specific protectomiRs can be revealed as potential therapeutic tools treating ischemia/reperfusion injury.